The dual roles of ferroptosis in digestive tract tumors: mechanisms, microenvironment regulation, and therapeutic integration with emphasis on immune interactions - Guo, Jiaojiao; Wang, Ziqing; Zhang, Yuhan; Xie, Chenyu; Chen, Yulong; Ma, Liangliang; Guo, Zhizhong; Zhang, Congcong (Frontiers in Immunology, 2026)
Malignant tumors of the digestive tract are a major global health burden, characterized by high incidence and mortality rates, limited treatment options for advanced patients, and poor prognosis. Ferroptosis is an iron-regulated form of cell death driven by lipid peroxide (LPO) accumulation, and it is closely linked to the occurrence and progression of various cancers. Ferroptosis plays a critical role in the proliferation, metastasis, drug resistance, and microenvironment regulation of digestive tract cancer. This article will systematically examine the dual roles of ferroptosis through the core concepts of mechanism analysis, microenvironment regulation, and immune interactions, while exploring the therapeutic potential of targeting ferroptosis in the treatment of gastrointestinal malignancies.